Paradiplomacy in Nigeria’s First Republic: The Uneasy Balance between Faith and National Interest - Babajimi Oladipo Faseke (Soshum: Jurnal Sosial dan Humaniora, 2022)
The study investigates the place of religion in the paradiplomacy that was practised in Nigeria’s first republic (1960-1966). It examines how the Northern regional government in Nigeria’s first republic engaged in external relations in furtherance of its narrow interests, which were mostly informed by Islam. During the first republic, Nigeria adopted a federal system of government in which the component units (or regions) wielded enormous influences. Some of these influences translated into external relations although foreign policy was constitutionally an exclusive preserve of the federal government. The practice of a regional government conducting its international relations while remaining within a sovereign nation falls under the ambit of ‘paradiplomacy’. Thus, this kind of subnational diplomacy is carried out with a view to promote subnational (or regional) interests. This raises the question of the compatibility of the interests of a subnational government with those of the national government, particularly in a country such as Nigeria that is multi-ethnic and multi-religious, with certain regions being predominantly Christian and others Muslim. The study adopts the theory of Social Constructivism as a framework and employs the use of qualitative analysis. The methodology is both historical and descriptive, with data derived from both primary and secondary sources. The primary sources employed include personal communications with retired diplomats as well as newspaper sources and archival materials sourced from the National Archives in Kaduna, Nigeria. Content analysis was also used to ensure accuracy and objectivity. Findings reveal that the government of the Northern Region pursued external policies that placed their region over and above the interest of the Federal Government to the extent of conflicts between the two entities, and religion was a telling factor in how this played out.